Conservative treatment by halo vest for a 63-year-old male with traumatic spondylolisthesis of the second cervical Levine-Edwards type 2 (hangman’s fracture): A case report - Effendi, Fajar Ivan; Utomo, Pamudji; Romaniyanto,; Prijosedjati, Raden Andhi; Yamani, Abdaud Rasyid (Indian Journal of Case Reports, 2020)
The hangman fracture is used to describe the traumatic spondylolisthesis of C2. The management strategies and surgical indications for executioner fractures are still controversial. However, conservative treatment has usually been effective in stable and neurologically normal patients when treated with appropriate immobilization in an extended position. We reported a case of a 63-year-old male patient with a hangman fracture on the second cervical vertebra that was treated with conservative treatment using a halo vest. After 1 month of halo vest application, the pain was decreased without neurological deficit evidence. The halo vest was released and a soft collar neck application was done. Three months after the removal of the halo vest and soft collar application, there were no pain and neurological deficit. We found evidence of displaced fracture of processus spinosus of the first and sixth cervical vertebrae and union of the third cervical vertebrae, union fracture of the pars interarticularis second vertebrae, and osteophytes on the anterior body fifth and seventh cervical with narrowing disc fifth-sixth cervical.